Regulation of Class A β-Lactamase CzoA by CzoR and IscR in Comamonas testosteroni S44 - Zhuang, Weiping; Liu, Hongliang; Li, Jingxin; Chen, Lu; Wang, Gejiao (Frontiers in Microbiology, 2017)
A genomic analysis of Comamonas testosteroni S44 revealed a gene that encodes a LysR family transcriptional regulator (here named czoR，czo for cefazolin) located upstream of a putative class A β-lactamase encoding gene (here named czoA). A putative DNA binding motif of the Fe-S cluster assembly regulator IscR was identified in the czoR-czoA intergenic region. Real-time RT-PCR and lacZ fusion expression assays indicated that transcription of czoA and czoR were induced by multiple β-lactams. CzoA expressed in Escherichia coli was shown to contribute to susceptibility to a wide range of β-lactams judged from minimum inhibitory concentrations. In vitro enzymatic assays showed that CzoA hydrolyzed seven β-lactams, including benzylpenicillin, ampicillin, cefalexin, cefazolin, cefuroxime, ceftriaxone and cefepime. Deletion of either iscR or czoR decreased susceptibility to cefalexin and cefazolin, while complemented strains restored their wild-type susceptibility levels. Electrophoretic mobility shift assays (EMSA) demonstrated that CzoR and IscR bind to different sites of the czoR-czoA intergenic region. Precise CzoR and IscR binding sites were confirmed via DNase I footprinting or short fragment EMSA. When cefalexin or cefazolin was added to cultures, czoR deletion completely inhibited czoA expression but did not affect iscR transcription, while iscR deletion decreased the expressions of both czoR and czoA. These results reveal that CzoR positively affects the expression of czoA with its own expression upregulated by IscR.